The growth and nitrogen uptake of Rhodes grass grown on soils with varying histories of legume cropping - Yaacob, Othman; Blair, Graeme J. (Springer Verlag, 1980)
Rhodes grass (Chloris oayana) was grown under glasshouse conditions on soils that had previously grown from 1 to 6 soybean (Glycine max) or Siratro (Macroptillium atropurpureum) crops. Soil mineral N contents at sowing were higher in Siratro-cropped than soybean-cropped soils and increased with cropping history. Yields of Rhodes grass at the first harvest (14 weeks) were related to soil mineral N levels at sowing by the relationship Y = 138.7 (l~0.917e~~)Grass grown on all soybean soils was responsive to N at both harvests (14 and 28 weeks). Grass grown on soils that had grown three or more Siratro crops was non-responsive to N at the first harvest but responses to N were recorded on all Siratro soils at the second harvest. The amount of N removed by the grass crops was small in relation to the total amount present in the soil system. This resulted in no change in soil total N levels over the two crop periods. These results highlight the need to study N dynamics in crop systems rather than continue to measure N pool sizes when evaluating the contribution of biologically fixed N to the nutrition of subsequent non-legume crops